Future Interior of the Past: An Air Terminal Comes of Age at Detroit-Willow Run - Kiely, Joss (UI Scholars Hub, 2025)
After the Second World War, manufacturing plants were no longer needed for wartime production levels, prompting the closure and repurposing of industrial facilities that became obsolescent overnight across the United States and in the manufacturing region of Southeastern Michigan. Located twenty miles west of Detroit, the Willow Run airfield in Ypsilanti was one such case. Best known for the massive B-24 Liberator manufacturing plant designed by Albert Kahn that opened in 1942 as Air Force Plant 31, the airfield played a key role in ending the war. Just to the south, a Kahn-designed hangar was loosely repurposed in 1946–1947 as a provisional passenger air terminal. A second renovation began in 1955, when the Airlines National Terminal Service Company (ANTSC) commissioned the firm of Yamasaki, Leinweber and Associates (YLA) to complete interior renovations to keep airlines from abandoning the airport in favour of the newer, larger, and more proximate to downtown, Detroit-Wayne Major Airport. Led by project architect Manfredi Nicoletti under the direction of Minoru Yamasaki, the renovation centred on a ceiling of suspended plastic coffers that created a spectacular backdrop against which passengers prepared to take flight. Even as the project came to fruition, it was clear that the future of the air terminal had already passed, and its eventual obsolescence was inevitable. Despite the project’s shortcomings, the interior renovation of the hangar-turned-terminal sheds light on the repurposing of large, flexible buildings and the employment of formal experimentation in the postwar United States.